Far-infrared radiation protects viability in a cell model of Spinocerebellar Ataxia by preventing polyQ protein accumulation and improving mitochondrial function - Chang, Jui-Chih (Sci Rep, 2016)
Far infrared radiation (FIR) is currently investigated as a potential therapeutic strategy in various diseases though the mechanism is unknown. Presently, we tested if FIR mediates beneficial effects in a cell model of the neurodegenerative disease spinocerebellar ataxia type 3 (SCA3). SCA3 is caused by a mutation leading to an abnormal polyglutamine expansion (PolyQ) in ataxin-3 protein. The consequent aggregation of mutant ataxin-3 results in disruption of vital cell functions. In this study, neuroblastoma cells (SK-N-SH) was transduced to express either non-pathogenic ataxin-3-26Q or pathogenic ataxin-3-78Q proteins. The cells expressing ataxin-3-78Q demonstrated decreased viability, and increased sensitivity to metabolic stress in the presence rotenone, an inhibitor of mitochondrial respiration. FIR exposure was found to protect against these effects. Moreover, FIR improved mitochondrial respiratory function, which was significantly compromised in ataxin-3-78Q and ataxin-3-26Q expressing cells. This was accompanied by decreased levels of mitochondrial fragmentation in FIR treated cells, as observed by fluorescence microscopy and protein expression analysis. Finally, the expression profile LC3-II, Beclin-1 and p62 suggested that FIR prevent the autophagy inhibiting effects observed in ataxin-3-78Q expressing cells. In summary, our results suggest that FIR have rescuing effects in cells expressing mutated pathogenic ataxin-3, through recovery of mitochondrial function and autophagy.